Measuring the economic benefits of advanced technology use for river flood forecasting - Lim, Siew Hoon; Ge, Yue; Jacobs, Jennifer M.; Jia, Xinhua (Journal of flood risk management, 2022)
As part of the Hudson Bay drainage system in North America, the Red River of the North Basin (RRB) has been subject to Spring River flooding in the past century. Previously, forecast errors had led to inadequate flood preparations that resulted in tremendous losses and overspending of taxpayer's dollars in flood response. National Aeronautics and Space Administration’s satellite microwave remote sensing technology offers improved snow water equivalent measurement information needed for spring flood forecasting in this region. This study evaluates the economic benefits of the technology use to the farm sector in the RRB. We found that farm support for the technology use for river flood forecast is overwhelming, and higher farm support yields higher willingness to pay for the product use. However, respondents who are content with the existing spring flood forecasts tend to have a lower valuation of the new product. Tellingly, landowners who lease to farm operators have noticeably zero perceived economic valuation of the product even though river flooding on their land could depress future land value.